1993
DOI: 10.1128/mcb.13.8.4657
|View full text |Cite
|
Sign up to set email alerts
|

Direct transcriptional stimulation of the ornithine decarboxylase gene by Fos in PC12 cells but not in fibroblasts.

Abstract: We have established rat PC12 pheochromocytoma cell lines stably expressing the estrogen-activatable transcription factor FosER to identify genes that can be regulated by c-Fos in this neuronal cell type. Induction of ectopic c-Fos activity in PC12 cells increased the mRNA levels of the ornithine decarboxylase (ODC) and tyrosine hydroxylase genes with similar kinetics and to the same maximal level as nerve growth factor treatment. In both cases the rate of transcription initiation was increased. Induction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…c-fos is one of many genes that are induced rapidly after serum stimulation of cells in culture (28,43,57 (39,52,71,87). To determine whether the Fos-Jun complexes in L1-3c-fos cells were capable of activating transcription of these putative target genes, Northern hybridization analysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…c-fos is one of many genes that are induced rapidly after serum stimulation of cells in culture (28,43,57 (39,52,71,87). To determine whether the Fos-Jun complexes in L1-3c-fos cells were capable of activating transcription of these putative target genes, Northern hybridization analysis was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The 940-bp PstI-EcoRI fragment was amplified by PCR with the two primers 5Ј-GCGCTGCAGATTC TTCTATATCTTCAAGATG-3Ј and 5Ј-GCGGAATTCTAAAATAAACTGA ACATCCATTA-3Ј. SP6 RNA transcripts of the three templates were in vitro translated in the presence of 3 H-labeled lysine (86 mCi/mmol; Amersham) in a nuclease-treated rabbit reticulocyte lysate as previously described (72). The protein products were analyzed by electrophoresis on an SDS-15% polyacrylamide gel, and the 3 H-labeled proteins were detected by sodium salicylate fluorography (16).…”
Section: Methodsmentioning
confidence: 99%
“…Deregulated expression of ODC and the subsequent changes in polyamine concentrations have been associated with several types of tumors (4, 8 -10). Recent studies indicate that overexpression of oncogenes such as myc (11)(12)(13), ras (14), fos (15), and mos (16) result in elevated levels of ODC expression. Importantly, two studies have shown that overexpression of ODC in fibroblasts induces neoplastic transformation and suggest a direct link between deregulation of ODC expression and oncogenesis (17,18).…”
mentioning
confidence: 99%